Margem de apreciação nacional: a anistia entre o "localismo" brasileiro e o "globalismo" interamericano - Barbosa, Natália Felizardo (2018)
This dissertation traces, through the jurisprudential analysis of the Inter-American Court of Human Rights and the Brazilian Federal Supreme Court, on amnesty matters, indications of the National Appreciation Margin Theory (founded by the European Court of Human Rights), using the discussion about the globalization of human rights and the counterpoint between "localisms" and "globalisms" - conformers of multicentric modern society - as a backdrop. In the construction of the research, the authoritative base criteria for the exercise of the margin of appreciation are established, defining the principles that establish and direct it, with special focus on the principle of subsidiarity as a counter-balance to the discretion of international law in front of the domestic law of the states, having as a parameter of definition the experience of the European supra-state entity. In order to do so, the hypothetical-deductive method is based on the assessment of the compatibility of the jurisprudence of the Courts studied at different levels of protection (dialogue and consensus) to ascertain the obedience of the domestic Court to the limits of its margin of deliberation regarding the application of international law and the capacity to maintain the human rights decision-making process at the closest level to the citizen as well as the establishment and provision of the largest and more effective protection of these rights in the Inter-American Regional System.